2013
DOI: 10.5505/bsbd.2013.69775
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Knowledge, Opinions and Professional Attitudes of Midwifery Students about Violence during Pregnancy

Abstract: Ebelik öğrencilerinin gebelikte şiddet konusundaki bilgi, görüş ve gebelikte şiddette karşı mesleki tutumlarını belirlemek amacıyla yapılmış tanımlayıcı bir araştırmadır. YÖNTEMLER: Araştırma İzmir'deki bir Sağlık Yüksekokulu'nun Ebelik Bölümü'nde eğitim gören hazırlık sınıfı hariç tüm öğrencilere (n: 312) uygulanmıştır. Araştırmaya katılmayı kabul eden ve formları eksiksiz dolduran toplam 271 öğrenciye ulaşılmıştır. Veri toplama araçları olarak; araştırmacılar tarafından literatür bilgileri doğrultusunda hazı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(4 reference statements)
0
3
1
1
Order By: Relevance
“…The attitudes of students in the experimental and control groups towards their occupational roles in addressing violence and women exposed to violence were evaluated at the beginning of the study, and it was determined that the students had traditional attitudes. In contrast to this study's findings, some previous studies found that students had contemporary and positive attitudes that were very different from traditional attitudes, while other studies, like the current study, found that students held a traditional point of view on violence against women . This finding may be due to students’ limited knowledge of the topic.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The attitudes of students in the experimental and control groups towards their occupational roles in addressing violence and women exposed to violence were evaluated at the beginning of the study, and it was determined that the students had traditional attitudes. In contrast to this study's findings, some previous studies found that students had contemporary and positive attitudes that were very different from traditional attitudes, while other studies, like the current study, found that students held a traditional point of view on violence against women . This finding may be due to students’ limited knowledge of the topic.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that undergraduate nursing training is the most appropriate period to provide nurses with the knowledge, attitudes, and skills needed to combat VAW . Additional studies that aimed to increase knowledge and abilities and promote helpful attitudes and abilities related to VAW have generally been conducted with healthcare professionals, although a few studies have been carried out with nursing students …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ebelik öğrencilerinin gebelikte şiddet konusundaki bilgi, görüş ve mesleki tutumlarının belirlenmesine yönelik çalışmada; öğrencilerin %60,9'u gebelikte şiddete yönelik eğitim almazken, %96,3'ünün bu konuda eğitim almak istemediği belirlenmiştir. 44 Şen'in, çalışmasında, sağlık profesyonellerinin tamamı gebelikte şiddeti bir sağlık sorunu olarak tanımlamakta ve %66,7'si şiddet belirtilerini tanılamada kendilerini yeterli görmektedirler. 45 Araştırmaya katılan hemşire ve ebelere çocuk istismarı ve ihmali konusunda daha fazla bilgilenme gereksinimi duyup duymadıkları sorulduğunda; %89,1'i gereksinim duyduğunu belirlenmiştir.…”
Section: Discussionunclassified